Characteristics, Treatment Complexity, and Outcome of Mixed-Phenotype Acute Leukemia in Children in a Low–Middle-Income Country - Salama, Maram; Ahmed, Sonia; Soliman, Sonya; El-Sharkawy, Nahla; Salem, Sherine; El-Nashar, Amr; Khedr, Reham; Lehmann, Leslie; Sidhom, Iman; El-Haddad, Alaa (Frontiers in Oncology, 2022)
Background Mixed-phenotype acute leukemia (MPAL) in children is an uncommon subtype of acute leukemia that cannot be definitively assigned to a specific lineage. There is no consensus on the best approach to therapy. Management is more complex in low–middle-income countries (LMICs). Aim To evaluate the clinicopathological characteristics and outcomes of patients with MPAL in a developing country. Patients and Methods A retrospective descriptive study of 42 pediatric patients newly diagnosed with MPAL from July 2007 until December 2017. Results The immunophenotyping was T/Myeloid in 24 patients (57.1%) and B/Myeloid in 16 (38.1%). Three subjects had MLL gene rearrangement, two had Philadelphia-positive chromosomes, and eight had FMS-like tyrosine kinase 3 (FLT3-ITD) internal tandem duplication (FLT3-ITD) with a ratio >0.4. Two subjects died before starting chemotherapy. Ten patients (25%) received acute lymphoblastic leukemia (ALL) induction, and all achieved complete remission (CR) with no induction deaths and no shift of therapy. Thirty patients (75%) started therapy with acute myeloid leukemia (AML) induction: five (16.6%) died during induction, 17 (56.7%) achieved CR, and 10 patients received maintenance ALL therapy after ending AML treatment. Four of the eight patients with induction failure were switched to ALL therapy. The 5-year event-free survival (EFS) and overall survival (OS) rates were 56.7% [standard error (SE): 8.1%] and 61% (SE: 8%), while the cumulative incidence of relapse was 21.7% (SE: 6.7%), with a median follow-up duration of 5.8 years. Patients treated with ALL-directed therapy had a 5-year EFS rate of 111 70% (SE: 14%) and OS rate of 78.8% (SE: 13%). Patients treated with ALL-directed therapy had a 5-year EFS rate of 70% (SE: 14.5%) and OS rate of 78.8% (SE: 13%). FLT3-ITD mutation showed a significantly lower 5-year EFS rate of 28.6% (SE: 17%) vs. 75% (SE: 9%) for the wild type, p = 0.032. Undernourished patients with a body mass index (BMI) z-score ≤-2 at presentation had a significantly lower 5-year EFS rate of 20% (SE: 17%) compared to 61.8% (SE: 8%) for patients with BMI z-score >-2, p = 0.015. Conclusion This study supports ALL-directed therapy for pediatric MPAL in a setting of LMIC. Given the poor outcome of FLT3-ITD, the role of FLT3 inhibitor needs to be explored in this subset of cases.